Pope Benedict XVI's motu proprio Intima Ecclesiae naturaChurch care for migrants - NECEL, WOJCIECH (Prawo Kanoniczne, 2013)
The motu proprio Intima Ecclesiae natura of Pope Benedict XVI from 11th November 2012 takes its place in the complete vision of the pastoral care for migrants presented in the instruction Erga migrantes caritas Christi published on 3rd May 2004 by the Pontifical Council for the Pastoral Care ofMigrants and Itinerant People. The document on which the author reflects has its concretisation in the Church's ministry to migrants. In a very special way it rounds out canon 213 of the Code of Canon Law and canon 16 of The Code of Canons of the Eastern Churches, and implicitly extends the institutional ministry of the Church for widely understood charitable assistance embracing all migrants regardless of their denomination or religion.